Indigenous Women and Customary Rights in Agrarian Conflicts: a Study of Ecofeminism - Saturi, Sapariah (Yayasan Jurnal Perempuan, 2015)
This paper narrates indigenous women, land rights, indigenous forests and the status of women’s marginalization in the agrarian conflicts in Nusantara. Forests are not only as natural resource, but for indigenous peoples, they were seen as culture. Rivers and swamps are not only a source of food. These are also the culture of indigenous women. Rivers and swamps are source for indigenous women in teaching their children to survive in nature. Since the presence of monoculture plantations, mining, etc., then they lose their cosmology (logos on beauty). Not only that the beauty is lost, but also acute environmental pollution that affect birth of disable infants.